Tuberculosis in Malaysia: a continuing surge - Nissapatorn, V.; Lim, Y.A.L.; Jamaiah, I.; Man Chin, H.; Ilyana, M.Z.; Nonaziah, M.Z.; Siti Hasifah, A.; Kuppusamy, I. (2007)
The substantial influx of foreign-born persons including immigrant population into the community becomes one of the postulated reasons to be elucidated relating to this so-called a disease without border in Malaysia. A total of 425 TB patients, including Malaysians and foreigners, were treated at the Institute of Respiratory Medicine from May to December 2003. TB was found relatively more often in foreign laborers and Malaysians with nonspecific occupations. Tuberculin skin test (TST) was used to screen for latent TB infection and a higher positive rate of TST was found in foreign compared to local patients. Chest X-ray findings showed a higher rate of abnormalities consistent with PTB, found in the majority of both groups. Lymph node biopsy and sputum culture were used significantly to detect the presence of M. tuberculosis and confirm the diagnosis of TB. EHRZ+B6 was significantly the most commonly used anti-tubercular drug regimen, found in both local and foreign patients. Foreign patients were more significantly associated with non-compliance to anti-tubercular therapy. Hepatitis was one of the most common adverse drug reactions found in local patients. The presence of a greater number of illegal migrants, who are highly mobile within the country as well as across borders, and who do not undergo any health screening, further complicates the national tuberculosis control program in the future.